Influences of Elevation on Growth and Yield of Strawberry in Thailand - Prapatsorn Riyaphan; Narongchai Pipattanawong; Suranant Subhardrabandu (Agriculture and Natural Resources, 2005)
Growth and yield of commercial strawberries (Fragaria x ananassa Duch.) cvs. Tioga and Tochiotome were compared under different elevations of 340, 720 and 1300 m at Royal Agricultural Research Center (RARC), Phang-da Royal Agricultural Station (PRAS), and Doi Pui Research Station (DPRS) respectively. Vegetative and reproductive growths were of significant differences. At RPAS, Tioga had greater plant fresh and dry weights and number of crown than those in the other locations, whereas DPRS had the longest root. In three elevations, Tochiotome was found to have first blooming before Tioga. At DPRS, Tioga had the highest number of inflorescences, while Tochiotome grown at PRAS had the greater number of runners. In this experiment, Tioga at DPRS produced the greatest fruit number and yield.